Hábitos alimenticios y su relación con el potencial cariogénico en la etapa de la primera infancia - Albán Zambrano, Pamela Lisbeth (2024)
Eating habits are comprised of both individual and group behaviours related to food utilization, and the analysis of dietary intake is presented as a valuable tool to obtain reliable and timely information, essential to assess the dental and nutritional condition in a group of individuals. Objective: To analyse the correlation between dietary habits and cariogenic potential in early childhood, using scientific evidence. Materials and Methods: A qualitative study was carried out by means of a scrupulous analysis based on articles from indexed journals such as: PubMed, LILACS, Science Direct, with the support of Boléan terms in order to carry out a more effective search. Results: Initially, a total of 106 articles were compiled, but from their selection based on exclusion and inclusion criteria, and with the PRISMA diagram, 9 substantial articles were selected. Conclusion: The need for proper nutrition from gestation to prevent dental disease in infants is highlighted, as well as the need to promote prevention of oral health care, brushing techniques, proper nutrition, among others, for both caregivers and parents, since educating the patients is the key to combating this major public health problem.